Adsorptive desulfurization by copper species within confined space - Tian, Wen-Hang (Langmuir : the ACS journal of surfaces and colloids, 2010)
Copper species were incorporated into SBA-15 by solid-state grinding precursor with as-prepared mesoporous silica (SPA). The obtained materials (CuAS) were well-characterized by XRD, TEM, N(2) adsorption, H(2)-TPR, IR, and TG and compared with the material derived from calcined SBA-15 (CuCS). Surprisingly, CuO up to 6.7 mmol·g(-1) can be highly dispersed on SBA-15 by use of SPA strategy. Such CuO forms a smooth layer coated on the internal walls of SBA-15, which contributes to the spatial order and results in less-blocked mesopores. However, the aggregation of CuO takes place in CuCS material containing 6.7 mmol·g(-1) copper, which generates large CuO particles of 21.4 nm outside the mesopores. We reveal that the high dispersion extent of CuO is ascribed to the abundant silanols, as well as the confined space between template and silica walls provided by as-prepared SBA-15. The SPA strategy allows template removal and precursor conversion in one step, avoids the repeated calcination in conventional modification process, and saves time and energy. We also demonstrate that the CuAS material after autoreduction exhibits much better adsorptive desulfurization capacity than CuCS. Moreover, the adsorption capacity of regenerated adsorbent can be recovered completely